Measured meals : nutrition in America - Mudry, Jessica J., 1974- (SUNY Press, 2009)
2009 CHOICE Outstanding Academic TitleAs nutritional studies proliferate, producing more and more knowledge about the connection between diet and health, Americans seem increasingly confused about what to eat to stay healthy. In Measured Meals, Jessica J. Mudry looks at the language used in the United States to communicate about health and nutrition, and reveals its effects on reframing, reshaping, and controlling what and how Americans eat. Analyzing the USDA and American federal food guidelines over the past one hundred years, Mudry shows how the language of nutrition has evolved over time. She critiques the trend of discussing food in terms of quantification--calories, vitamins, and serving sizes. She also examines how organizations such as the USDA attempt to legislate a healthy diet by mandating quantities of food based on measurable nutrients, revealing the power of language to make meaning and influence social action.